Non-immune hydrops fetalis - Murat Yurdakök (Hygeia Press di Corridori Marinella, 2014)
Non-immune hydrops fetalis (NIHF) refers to hydrops in the absence of maternal circulating red-cell antibodies, and constitutes up to 90% of all described hydrops fetalis cases. One-third of hydropic fetuses are discovered incidentally during prenatal sonography in the first or second trimester of gestation. Although hydrops is a fetal condition, in many cases there are associated maternal findings, such as preeclampsia, polyhydramnios, and mirror syndrome (generalized maternal edema, that 'mirrors' the edema of the hydropic fetus and placenta). NIHF should be seen as a symptom or clinical phenotype rather than as a disorder, and considered as a non-specific, end-stage status of a wide variety of disorders. Numerous disorders including fetal disorders, maternal diseases (e.g., severe maternal anemia, diabetes and maternal indomethacin use) and placental/cord abnormalities have been associated with NIHF. Despite extensive investigations, the etiology on NIHF may remain unknown in 15% to 25% of patients, even after an autopsy has been performed. Chromosomal abnormalities are the cause of NIHF in 25-70% of the cases. Therefore, fetal or neonatal chromosome analysis is indicated in all cases of NIHF. Abnormalities of the cardiovascular system are responsible for as many as 40% of cases of NIHF. Thoracic abnormalities increase intrathoracic pressure and can obstruct venous return to the heart, leading to peripheral venous congestion, or they may obstruct the lymphatic duct, resulting in lymphedema. Fetal anemia accounts for 10-27% of hydrops. To evaluate the risk of fetal anemia, Doppler measurement of the middle cerebral artery peak systolic velocity should be performed in all hydropic fetuses after 16 weeks of gestation. Parvovirus B19 is the most common infectious agent associated with hydrops. Even in persistent severe anemia, the prognosis is generally good if the fetus is supported by intrauterine fetal transfusions. The development of hydrops in fetuses with a TORCH infection is a poor prognostic indicator. Although hypoproteinemia is frequently proposed as one of the causes of hydrops fetalis, recent studies show that hypoalbuminemia is unlikely to cause the initial development of hydrops. However, it seems to occur as a secondary effect in the cascade of hydrops, and might be the trigger for mild hydrops to evolve into severe hydrops. In addition, not all infants with hypoproteinemia become hydropic, and hydrops fetalis is uncommon in congenital nephrotic syndrome and congenital analbuminemia. In the pathogenesis, inherited metabolic disorders, especially lysosomal storage diseases, are more common than previously thought. Inherited metabolic disorders must be always thought when investigating cases of recurrent NIHF in the same family. It is very important to examine the placenta carefully in cases where hydrops or ascites are present at birth or detected by ultrasound, especially in the transient form. Even if a family does not agree to autopsy, placental examination may be done. Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou